Empowering Rural Women Through Digital Marketing and Financial Management Education Towards Independent and Sustainable Businesses - Deliyanti Simbolon; M.Fahriyal Aldi; Sipnarong Kanchanawongpaisan; Muhammad Hafiz Abd. Rashid; Phan Bao Giang; Najla Najla; Selfina Selfina (Eastasouth Institute, 2025)
Community service activities aim to improve understanding, skills, and confidence in utilizing digital technology and managing business finances effectively. Empowerment activities aim to create independent, resilient, innovative, and sustainable women entrepreneurs, so that they can have a positive impact on family welfare and the broader village economy. In Pematang Johar Village, weak digital literacy and poor financial management have caused many village women's businesses to stagnate, even at risk of stopping midway. Through intensive training and mentoring provided, the implementation team introduced and trained digital marketing and financial management according to the needs of the Village. The implementation methods included observation, digital marketing training, business financial management training, mentoring, and program evaluation. The results of the activities showed a significant increase in the understanding of digital marketing and business financial management. The activities are expected to improve product promotion and more organized financial management for women in Pematang Johar Village. Integrated empowerment is important to support sustainable businesses.